Bilge Olgaç sineması - Kuşaklıoğlu, Mevlüde (My University, 2014)
Bu çalışmanın amacı; Türk Sineması’nda kadın yönetmen ve kadın olma durumlarına eleştirel bir bakış açısı getirmektir. Bu eleştirel bakış açısı da Bilge Olgaç Sineması’nda ‘bakış’ ve ‘cinsiyet temsili’ ile sağlanmıştır. Konunun sağlam bir zemin üzerine oluşturulması için öncelikle yönetmen Bilge Olgaç’ın aktif olarak film yaptığı 1960-2000 yılları arasında Türk Sineması’nın genel yapısı ve özellikleri incelenmiştir. Ardından Bilge Olgaç’ın biyografisine yer verilmiş ve filmlerini daha iyi yorumlayabilmek için özgün film dili incelenmiştir. Bilge Olgaç Sineması ile ilgili temel bir kaynak oluşturmak amacıyla tüm filmleri ile ilgili temel bilgi ve özetlerin yer aldığı filmografi bölümüne yer verilmiştir. Tez çalışmasının kuramsal kısmını oluşturan son bölümde ise ‘bakış’ kavramsal olarak incelenmiş ve toplumsal özellikler göz önünde bulundurularak cinsiyet temsili ile ilişkilendirilmiştir. Bilge Olgaç Sineması’nda ‘bakış’ ve ‘bakışın değişimi’ni daha iyi yorumlayabilmek için, farklı dönemleri yansıtan dört film ‘bakış’ kavramı ile analiz edilmiştir. Sonuç olarak, Türk Sineması’nın sayılı kadın yönetmenlerinden olan Bilge Olgaç’ın sinemasında kadın, kadın temsili, erkek egemen söylem vs. gibi toplumsal konular incelenmiştir. Bakış, Türk Sineması, Cinsiyet, Kadın Temsili, Bilge Olgaç…

The purpose of this study is to have a critical approach about the female film directors in Turkish cinema as well as the status of being woman. The critical approach is provided by the “perspective” and “gender representation” in Bilge Olgaç filmpograhy. Primarily the general structure and features of Turkish cinema in the period of 1960-2000 in which director Bilge Olgaç has been active is examined in order to place the topic on the solid ground. Then biography of Bilge Olgaç is depicted and especially her original style and language is examined in order to construe her films in better way. Section of filmography is added related to her all films synopsis in order to develop a main source for the Bilge Olgaç Cinema. In the last section of thesis study which is included by therotical ground the “perspective” is examined conceptually and make it related to the gender representation by taking the social characteristics into consideration. In order to examine the “perspective” and “change of perspective” in the Bilge Olgaç cinema in better way. Four films reflecting different periods are analyzed by the “perspective” concept. Consequentially, social topics such as woman, representation of women and male dominated style are examined in the Bilge Olgaç Cinema who is a limited female director in Turkish Cinema. Key Words: Perspective, Turkish Cinema, Gender, Representation of Woman, Bilge Olgaç…
Keywords: Sinema